Guideline-Driven Management of Hypertension: An Evidence-Based Update - Carey, Robert M. (Circ Res, 2021)
Several important findings bearing on the prevention, detection and management of hypertension have been reported since publication of the 2017 American College of Cardiology (ACC)/American Heart Association (AHA) Blood Pressure (BP) Guideline. This review summarizes and places in context the results of relevant observational studies, randomized clinical trials and meta-analyses published between January, 2018 and March, 2021. Topics covered include BP measurement, patient evaluation for secondary hypertension, cardiovascular disease (CVD) risk assessment and BP threshold for drug therapy, lifestyle and pharmacologic management, treatment target BP goal, management of hypertension in older adults, diabetes mellitus, chronic kidney disease, resistant hypertension, and optimization of care using patient, provider and health system approaches. Presenting new information in each of these areas has the potential to increase hypertension awareness, treatment and control which remain essential for the prevention of CVD and mortality in the future.